Development of mathematical model for aerosol deposition under jet condition. (July 2020) - Yan, Xu; Zhou, Yanmin; Diao, Han; Gu, Haifeng; Li, Yingzhi
Highlights: A visualized narrow channel is designed to observe the air-liquid interface pattern and measure the scale of wave peaks and wavelengths. A new model of aerosol removal in jet flow condition is established by considering both of gas-liquid boundary and entrainment droplets simultaneously. The liquid drop size of the unit interval is considered to be logarithmic normal distribution with upper limit. The accuracy of the new model is verified with published experimental data, and the aerosol removal efficiency in some extended conditions are predicted. Abstract: Gas-liquid jet flow is a typical phenomenon in severe reactor accidents. It is great significance to evaluate the scrubbing efficiency of aerosols in jet flow conditions reasonably for the analysis of source terms and also adopting mitigation measures. In this paper, a visualization experiment is carried out, and a mathematical model is developed based on the experiment results by considering the deposition mechanism from fluctuation interface and entrainment droplets simultaneously. Model verification results show that in case of gas injection flow under lower velocity, fluctuated gas-liquid interface play a dominant role on aerosol removal, but the jet flow condition has a weak filtration effect on aerosols with small particle size. While in case of high velocity, entrainment droplets may play a dominant role on aerosols removal and the scrubbing efficiency gradually loses its sensitivity to particle size and maintain upon 99%.